2022
DOI: 10.3892/ol.2022.13257
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analyses of the expression profiles of INSM1, ATRX, DAXX and DLL3 in solid papillary carcinomas of the breast

Abstract: Solid papillary carcinoma (SPC) is a rare but distinct clinicopathological feature of breast cancer characterised by frequent neuroendocrine differentiation. Insulinoma-associated protein 1 (INSM1) is a useful neuroendocrine marker for various neuroendocrine tumours. α-thalassemia/mental retardation syndrome X-linked protein (ATRX) and death domain-associated protein (DAXX) are useful prognostic markers for patients with pancreatic neuroendocrine tumours. However, to the best of our knowledge, few studies have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Low levels of DAXX expression associated with lower DFS but not OS [27]. In solid papillary carcinoma (SPC) patients, loss of DAXX expression was significantly associated with lymphatic invasion [28].…”
Section: Breastmentioning
confidence: 99%
See 1 more Smart Citation
“…Low levels of DAXX expression associated with lower DFS but not OS [27]. In solid papillary carcinoma (SPC) patients, loss of DAXX expression was significantly associated with lymphatic invasion [28].…”
Section: Breastmentioning
confidence: 99%
“…39 solid papillary carcinoma (SPC) specimens (18 SPC in situ and 21 SPC invasive) -IHC Loss of DAXX expression was significantly associated with lymphatic invasion [28] HJURP 44 in situ breast carcinoma specimens -IHC…”
mentioning
confidence: 99%
“…Additionally, survival analysis on cervical carcinoma suggested that the loss-offunction of ATRX was associated with a better prognosis in patients treated with chemo-radiation [12]. However, to date, the potential role of ATRX in BC, especially its role in the HER2-/HR+ subtype, remains inadequately explored [15]. Dysregulated transcription factors (TF) mediate aberrant gene expression, which is the hallmark properties of drug resistance in tumours [16].…”
Section: Introductionmentioning
confidence: 99%